Intravenous Iron sucrose and change in hemoglobin, ferritin, and oxidative stress markers among moderately anemic pregnant women attending a secondary care level Hospital in Northern India - Olivia Marie Jacob; Shashi Kant; Partha Haldar; Ravneet Kaur; Vatsla Dadhwal; Shyam Prakash (Wolters Kluwer Medknow Publications, 2020)
Background: Intravenous iron is associated with oxidative stress, and very few studies have assessed change in oxidative stress markers post infusion. Objectives: The study aimed to measure the change in levels of hemoglobin (Hb), serum ferritin, and select oxidative stress markers (malondialdehyde [MDA], superoxide dismutase [SOD], and ferric reducing ability of plasma [FRAP]) 4 weeks following the administration of intravenous iron sucrose (IVIS) among moderately anemic pregnant women who were attending a secondary-level health-care facility, Haryana, North India. Methods: An observational study was conducted (May 2016 to Jan 2018) among pregnant women receiving intravenous iron sucrose i.e., IVIS (300 mg per dose) diluted in 300 mL of normal saline over 20-45 min and were followed up for a period of 4 weeks after the last dose of IVIS (end line). The study outcomes were measured in the levels of Hb, serum ferritin, MDA, SOD, and FRAP from the baseline to the end line. Results: The mean (95% confidence interval) change in the Hb and serum ferritin level 4 weeks after the last dose of IVIS was an increase of 2.5 (2.1-3.0) g/dL (P < 0.001) and 63.0 (44.7-81.3) ng/mL (P < 0.001), respectively. There were no significant changes (baseline to end line) in mean (standard deviation [SD]) MDA level and mean (SD) FRAP level. The mean (SD) SOD level declined significantly (2.2 [0.4] U/mL to 1.6 [0.5] U/mL [P < 0.001]). No life-threatening adverse events were encountered during the study. Conclusion: IVIS was well tolerated and effective in treating moderate anemia in pregnancy. Body iron store was replenished following IVIS administration. There was no increase in oxidative stress following IVIS therapy.